Knowledge sharing in communities of practice : examining usefulness of knowledge from discussion forums versus repositories - Boh, Wai Fong (2014)
With the prevalent use of virtual Communities of Practice (CoPs) in organizations to link networks of individuals located in disparate geographical areas, information communication technologies (ICTs) take on a crucial role in supporting CoPs. In this paper, I examine the role that ICTs play in supporting knowledge sharing in virtual CoPs. In particular, I examine the use of two key types of ICTs -- knowledge repositories and online discussion forums. Based on the perceived cost of using these two types of ICTs, I theorize about how various factors would differ in their influence on knowledge sourcing from knowledge repositories and from online discussion forums. Two event-driven surveys were conducted with members of a CoP in a consulting firm to test the hypotheses. The surveys were conducted when CoP members downloaded documents from the knowledge repository and when CoP members posted inquiries and received responses in an online discussion forum. The results of the event-driven surveys partially support the hypotheses and show the importance of understanding the perceived costs of using the ICT to support knowledge reuse when we study knowledge sharing in virtual CoPs and in other settings that depend significantly on technological tools for knowledge sharing.